Light metals 2012 : proceedings of the technical sessions presented by the TMS Aluminum Committee at the TMS 2012 Annual Meeting & Exhibition, Orlando, Florida, USA, March 11-15, 2012 - Suarez, Carlos E. (Springer, 2016)
An update of the definitive annual reference source in the field of aluminum production and related light metals technologies, a great mix of materials science and practical, applied technology surrounding aluminum, bauxite, aluminum reduction, rolling, casting, and production.
Includes indexes.
Keywords: Light metals -- Metallurgy -- Congresses.; Materials science.; Lightweight construction.; Building, Iron and steel.; Materials.; Metals.; elektronické knihy; electronic books